Implementasi Sistem Informasi Manajemen melalui Platform Merdeka Mengajar untuk Meningkatkan Kompetensi Guru Sekolah Dasar - Ahmad Hariandi; Kartini Putri Dewi; Revina Voseka; Sonya Arvita Sari; Noly Ramawani (Journal on Education, 2023)
The need for greater and higher quality human resources is currently the demand of every country fighting for its civilization. In this regard, a special forum was created for teachers to develop their potential and skills as teachers. The purpose of this study is to describe the use of MMP (Merdeka Mengajar Platform) to improve the competence of primary school teachers. The research method is descriptive qualitative research with a literary research approach. This study analyzes the use of self-learning platforms to improve teacher competence by looking at various books and journals related to the subjects addressed. The findings of this study show that the use of MMP as a tool to improve teacher competence in elementary schools is very important and contributes to learning. In addition, teachers get services where they can improve their skills, increase their understanding and get many innovations and creative ideas through the features provided. However, researchers continued to find weaknesses in MMP, namely the lack of teachers in using MMP and implementation strategies that needed further development.